Factors Affecting Social Emotional Of Early Childhood - Syifaushudur Harefa; Regita Indah Cahyani; Fildzah Azrina; Nur Hamidah (Proceeding International Seminar of Islamic Studies, 2021)
: Emotional social development is a child's sensitivity to understand the feelings of others when interacting in everyday life. Social development in children is characterized by the child's ability to adapt to the environment, make friends that involve emotions, thoughts and behavior. The method used in this study is a descriptive qualitative method, and the data collection method uses a variety of literature related to this study. The data sources in this research are journals, research reports, books, etc. which have relevance to the research topic. The object of this research is related to the social and emotional development factors of children which aim to determine what factors affect the child's social and social development. Keywords :Early childhood, Social, emotional factors.